Antioxidant and antiproliferative properties of some 2- (4h- [1,2,4] Triazol-3-Yl-sulfanyl) -acetamide derivatives - Demir, Selahattin; Pekdemir, Sibel Selçuk; Keser, Serhat; Karatepe, Arzu; Koparır, Metın; Karatepe, Mustafa (My University, 2021)
In this study, the cytotoxic effects of some 2- (4H- [1,2,4] triazol-3-yl-sulfanyl)-acetamide derivatives compounds on the L1210 rodent leukemia cancer cell line were investigated. At the same time, the effect on MDA concentration showing the degree of lipid peroxidation in Saccharomyces cerevisiae yeast cells treated with these compounds and vitamin A, E and C values were investigated. In addition, the antioxidant properties were investigated by the DPPH radical scavenging method. It was determined that the compounds did not make a statistically significant difference in the A, E, C vitamin levels and MDA concentrations in Saccharomyces cerevisiae yeast cells. It was observed that the study groups did not show antioxidant activity in DPPH radical scavenging activity results. Based on the antitumor activity results, the compounds were generally found to have an effective cytotoxic activity on the L1210 cell line.
Keywords: Antioxidant; anticancer